Analysis Influence of Market Orientation and Digital Marketing Capability on The Marketing Performance of Digital Culinary Sector MSMEs In Surabaya City - Whindya Rahmadi Muhammad; Tias Andarini Indarwati (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
Micro, Small, and Medium Enterprises (MSMEs) are business units that have an omzet under 2.5 billion rupiah per year and have assets under 10 billion rupiah. However, MSMEs take an important role in the Indonesian economy because they have contributed to PDP Indonesia by 60.3%. This Performance was achieved because MSMEs have implemented market orientation and have digital marketing capability. But, with the ability the marketing Performance of MSMEs has actually by 11.6% compared to 2021. So this study aims to reveal whether there is a significant influence between market orientation and digital marketing capability on Performance. digital MSME marketing in the Surabaya culinary sector. In sampling for this study, use Purposive  Sampling.  The data taken n  this study was through primary data by distributing questionnaires to as many as 99 respondents who were selected based on the criteria of UMKM in the Surabaya culinary sector who were at least 1 year had already been digitally transformed. Data were analyzed using multiple linear regression by using SPSS25 and the results showed that there was an effect of market orientation and digital marketing capabilities on the marketing Performance of digital MSMEs in Surabaya's culinary sector.